2017
DOI: 10.1002/aenm.201602567
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten Disulfide Catalysts Supported on a Carbon Cloth Interlayer for High Performance Li–S Battery

Abstract: liquid electrolyte. The ability to plate/strip a lithium anode from an organic-liquid electrolyte has recently been demonstrated. [2] However, the limited capacities of the transition-metal oxides used as cathodes [3] have created a growing interest in the lithium-sulfur (Li-S) battery [4] because sulfur (S 8 ) units are reduced to dilithium sulfide (Li 2 S) to give a theoretical capacity of 1675 mA h g −1 . However, a principal impediment of the sulfur cathode has been the existence of intermediate Li 2 S x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
228
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 329 publications
(232 citation statements)
references
References 50 publications
2
228
0
Order By: Relevance
“…Note that different super P contents were used according to the fixed sulfur content (Table S1 For an in-depth understanding on the electrochemical behavior of each electrode, the discharging reaction was investigated in three separate regimes (S 8 dissolution, polysulfide conversion, and Li 2 S formation) as depicted in Figure S11 in the Supporting Information, based on the theoretical investigation by Park and co-workers [35,[53][54][55] Upon discharge, solid S 8 first converts to soluble polysulfide intermediates, which constitutes the "dissolution" step. Detailed cell preparation is described in the Experimental Section.…”
Section: Resultsmentioning
confidence: 99%
“…Note that different super P contents were used according to the fixed sulfur content (Table S1 For an in-depth understanding on the electrochemical behavior of each electrode, the discharging reaction was investigated in three separate regimes (S 8 dissolution, polysulfide conversion, and Li 2 S formation) as depicted in Figure S11 in the Supporting Information, based on the theoretical investigation by Park and co-workers [35,[53][54][55] Upon discharge, solid S 8 first converts to soluble polysulfide intermediates, which constitutes the "dissolution" step. Detailed cell preparation is described in the Experimental Section.…”
Section: Resultsmentioning
confidence: 99%
“…[50][51][52][53][54] However, both the nitrides and sulfides demonstrate a weaker adsorption ability which exerts an important influence on electrochemical performance in the adsorptioncatalysis synergy system. The high conductivity is the main advantage of nitrides as compared with sulfides, which can enable the fast electron transfer and thus improve the electrochemical utilization of active sulfur.…”
Section: Catalysis Superiority Synergymentioning
confidence: 99%
“…Typically, ZnS, [50] VS 2 , [51] Co 3 S 4 , [52] VS 4 , [53] and MoS 2 [54] are the most common components, which have been demonstrated with great potential in alleviating the LiPSs diffusion out of the sulfur hosts. Typically, ZnS, [50] VS 2 , [51] Co 3 S 4 , [52] VS 4 , [53] and MoS 2 [54] are the most common components, which have been demonstrated with great potential in alleviating the LiPSs diffusion out of the sulfur hosts.…”
Section: Catalysis Superiority Synergymentioning
confidence: 99%
“…[139] Yu et al reported hierarchical core-shell-like MnO 2 nanostructures decorated MnO 2 hexagonal nanoplate arrays uniformly grown on carbon cloth fibers using a novel one-step electrochemical deposition method. [140] Later, V 2 O 5 nanoparticles encapsulated in 3D networked porous carbon matrix, [141] needle-like Fe 3 O 4 and flake-like NiO, [142] layered tungsten disulfide (WS 2 ) [143] and cubic phase CoSe 2 , [144] have been also grown on carbon cloth. Recently, ternary transition metal oxides/sulfides have attracted significant research interest, due to their widely promising www.advancedsciencenews.com application in many fields.…”
Section: Template-assisted Approachmentioning
confidence: 99%
“…3D nitrogen-doped porous CNFs can be prepared using our CNF gel without adding any activation as the electrodes of supercapacitors, which exhibit hierarchical structure with reasonable distribution of mesopores and micropores. Compared to the carbon materials with single-sized pores, the [57][58][59][60][61][62][63][64]72] High surface areas; low volume density Thermal transformation approach CNF gels derived from thermal transformations of BC [16,70,85,86,[102][103][104][105][106][107][108][109][110][111][112][113] CVD technique 3D CNF/graphene networks [116] 3D CNF films Template-assisted approach Carbon cloth, carbon papers and carbon fiber felt-based 3D CNF films [128][129][130][131][132][133][134][135][136][137][139][140][141][142][143][144][145][146][147]…”
Section: Supercapacitorsmentioning
confidence: 99%